Gamifying Higher Education: A Phenomenological Study of Wayground™ Integration on Pedagogy and Student Engagement - Patur Rahman; Fatmawati Akhmad; Nurwahida Nurwahida (Medan Resource Center, 2025)
This study examines the integration of Wayground™, a gamified online quiz platform, in higher education by exploring its pedagogical implications and its influence on student engagement. The study addresses how Wayground™ reshapes lecturers’ pedagogical practices and how students perceive and respond to gamified learning environments. Adopting a mixed-methods approach, the research draws on qualitative data from semi-structured interviews with a lecturer to capture lived pedagogical experiences, complemented by quantitative data from student questionnaires measuring academic motivation, engagement, and perceived learning effectiveness. The qualitative analysis identified six central themes, including gamification-based classroom management, assessment practices, technical challenges, pedagogical benefits, perceived drawbacks, and comparisons with conventional paper-based assessments. Quantitative findings indicate that students generally report heightened engagement, increased interest, and stronger academic motivation when Wayground™ is incorporated into classroom activities. The study argues that Wayground™ functions as an effective pedagogical tool that fosters interactive learning and enhances instructional effectiveness in higher education, while also requiring careful consideration of technical and contextual constraints to ensure sustainable and meaningful implementation.